Pengaruh Belanja Modal Terhadap Pertumbuhan Kinerja Keuangan Daerah Dengan Pendapatan Asli Daerah sebagai Variabel Intervening pada Kabupaten dan Kota di Provinsi Jawa Tengah Tahun 2011-2013 - Arba, Hilya; , Drs. Atwal Arifin, Ak.,M.Si (2016)
The aim of this research is to know the influence of the Capital Expenditure to the Regional Financial Performance Growth with Local Revenue as the Intervening Variable in the Regency and the Municipality in Central Java Province year 2011-2013. The population of this research is all of the Regency and Municipality in Central Java Province. Sampling technique that is used is purposive sampling technique and the number of sample is 76 Regency and Municipality. The data of this research is secondary data from Regional Income and Expenditure Budget Realization Report of Regency and Municipality in Central Java Province year 2011-2013. The finding of this research is that the capital expenditure has no influence to the regional financial performance growth, however, the capital expenditure indirectly influences to the regional financial performance growth by means of local revenue as intervening variable.